2006
DOI: 10.1007/s00125-006-0437-7
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan inhibits AGE-induced C-reactive protein production through downregulation of the receptor for AGE via peroxisome proliferator-activated receptor-gamma activation

Abstract: Aims/hypothesis C-reactive protein (CRP), an acute-phase reactant produced mainly by the liver, is elevated in diabetes, thus contributing to the development and progression of atherosclerosis. However, the molecular mechanism underlying the elevation of CRP in diabetes is not fully understood. Since a crosstalk between AGE and angiotensin II (Ang II) has been proposed in the pathogenesis of accelerated atherosclerosis in diabetes, we examined here whether and how telmisartan, a unique Ang II type 1 receptor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 10 publications
1
66
0
Order By: Relevance
“…Indeed, in a recent study, Yoshida et al [19] demonstrated that telmisartan improves IR in advanced glycation endproduct (AGE)-exposed human hepatoma (Hep3B) cells by decreasing serine phosphorylation and enhancing tyrosine phosphorylation of insulin-receptor substrate-1 but, when antagonized with an inhibitor of PPARγ, it loses these properties. Other animal studies [20][21][22][23] provided additional evidence of properties of telmisartan linking it to PPAR modulation that can account for its effects in steatohepatitis, for example a partial PPAR-α agonist activity which seems to be restricted to the liver, regulating serum adipokines with increased adiponectin and decreased resistin levels, and even anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent study, Yoshida et al [19] demonstrated that telmisartan improves IR in advanced glycation endproduct (AGE)-exposed human hepatoma (Hep3B) cells by decreasing serine phosphorylation and enhancing tyrosine phosphorylation of insulin-receptor substrate-1 but, when antagonized with an inhibitor of PPARγ, it loses these properties. Other animal studies [20][21][22][23] provided additional evidence of properties of telmisartan linking it to PPAR modulation that can account for its effects in steatohepatitis, for example a partial PPAR-α agonist activity which seems to be restricted to the liver, regulating serum adipokines with increased adiponectin and decreased resistin levels, and even anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…16 Besides, telmisartan inhibited AGE-induced ROS generation via PPAR␥ activation in human hepatoma Hep3B cells. 36 PPAR␥, a ligand-activated transcription factor belonging to the nuclear receptor superfamily, regulates gene expression of key proteins involved in lipid metabolism, vascular inflammation, and proliferation, providing protection against atherosclerosis and coronary events. 37 Recently, Yang et al 38 have demonstrated that PPAR␥ activation lowers the ROS levels through coordinated transcriptional control of a set of proteins and enzymes involved in ROS metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…that some ARBs (including OLM) (Yoshida et al 2006;Yamagishi et al 2008) and nifedipine, another dihydropyridine CCB, also suppress the AGEs-RAGE expressions (Matsui et al 2010). It was previously reported that OLM reduces serum levels of the RAGE ligands, such as AGEs (Nangaku et al 2003) and N-(epsilon)-carboxymethyllysine (CML) (Honda et al 2012), and that AZL also reduces AGEs (Nakamura et al 2011).…”
Section: Anti-oxidant Effects Of Olm Plus Azlmentioning
confidence: 99%